2019
DOI: 10.1101/863100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential response trajectories to acute exercise in blood and muscle

Abstract: A physically active lifestyle is essential for maintaining health, and is a powerful way to prevent chronic disease. However, the molecular mechanisms that drive exercise adaptation and transduce its beneficial effects, are incompletely understood. Here, we combined data from 49 studies that measured the whole transcriptome in humans before and after exercise to provide the power to draw novel observations not seen in any individual study alone. The resulting curated and standardized resource includes samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…However, increasing evidence demonstrates that sex differences in signaling and gene regulatory response of skeletal muscle to exercise training likely exist (64). A recent large-scale metaanalysis on this topic pooled the findings of multiple studies encompassing different exercise modalities (65). Together, these studies reported 247 differentially expressed genes in response to exercise between males and females (65).…”
Section: Altered Exercise-induced Gene Expression In Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing evidence demonstrates that sex differences in signaling and gene regulatory response of skeletal muscle to exercise training likely exist (64). A recent large-scale metaanalysis on this topic pooled the findings of multiple studies encompassing different exercise modalities (65). Together, these studies reported 247 differentially expressed genes in response to exercise between males and females (65).…”
Section: Altered Exercise-induced Gene Expression In Skeletal Musclementioning
confidence: 99%
“…A recent large-scale metaanalysis on this topic pooled the findings of multiple studies encompassing different exercise modalities (65). Together, these studies reported 247 differentially expressed genes in response to exercise between males and females (65). However, whether or not metabolic disease may differently affect gene expression in response to exercise in males and females remains unclear, and should be a topic for future study.…”
Section: Altered Exercise-induced Gene Expression In Skeletal Musclementioning
confidence: 99%
“…Despite this, there are relatively few trials investigating the effects of exercise on gene regulatory mechanisms of healthspan and lifespan. Of those that have been performed, most examine the effects of a single bout of exercise on gene expression, rather than repeated bouts (Amar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%